Pengaruh Orientasi Pasar dan Perilaku Kewirausahaan Terhadap Kepekaan Perusahaan Dan Implikasinya Pada Kinerja Perusahaan: Studi pada Penyalur Sepeda Motor di Indonesia - Adinoto Adinoto (Universitas Multimedia Nusantara, 2010)
This research, test the impact of the market orientation and entrepreneurship behavior to organization responsiveness and implication to company’s performance by utilizing the data of AISI (Asosiasi Industry Sepeda Motor Indonesia) motorcycle dealers companies’ in Indonesia. Moreover, As the tools for this analysis are using SPSS 16.0 and LISREL 8.8. There are few results from this research. Firstly, market orientation does not have significant impact towards entrepreneurship behavior. Secondly, market orientation does have positive and significant impact towards company’s responsiveness. Thirdly, entrepreneurship behavior does have positive and significant impact towards company’s responsiveness. Fourthly, the company’s responsiveness does have positive and significant impact towards company’s performance. Keywords: Dealership, Market Orientation, Entrepreneurship, trust, responsiveness, Performance